Finite-Control-Set Predictive Current Control Based Real and Reactive Power Control of Grid-Connected Hybrid Modular Multilevel Converter - Rashmi Ranjan Behera; Amarnath Thakur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper proposes the grid application of modified three-phase topology of Modular Multilevel Converter (MMC) using finite-control-set predictive control. This topology has reduced number of switch counts compared to the conventional MMC, eliminates the problem of circulating current and having higher efficiency. A single dc source is required to produce sinusoidal outputs. The number of sub-modules (SMs) in this topology is half of the SMs required in case of MMC, in addition to a single H-bride circuit per phase. The finite-control-set predictive current control scheme for the grid connected dc source through the Hybrid Modular Multilevel Converter (HMMC). This controller controls the desired real and reactive power demand of the grid instantaneously. The simulation study of a three phase grid connected system has been done in Matlab/Simulink and the results are provided for the different real and reactive power demands, to validate the concepts.